Indikasi mineralisasi epitermal emas bersulfi da rendah, di Wilayah Kecamatan Bonjol, Kabupaten Pasaman, Sumatera Barat - Hamdan Z. Abidin; Bhakti H. Harahap (Indonesian Journal on Geoscience, 2007)
http://dx.doi.org/10.17014/ijog.vol2no1.20075Bonjol gold prospect, known as Old Dutch Gold mine, consists of several ore bodies (Malintang, Balimbing, Lubang Sempit, Lubang Belanda and Lubang Perak). The deposit hosts within the altered volcanic rocks known as Gunung Amas Formation of Early Miocene age (9.3 ± 0.4 - 11.9 ±1.0 Ma). This formation consists of various rock types such as rhyolitic tuff, volcanic breccia, dacitic tuffs and rhyolites. These rocks are moderate to strongly alter. Mineralogy of the deposit consists of gold and silver with minor pyrite, sphalerite and galena. Besides this, hematite, jarosite and manganese are also present as supergene minerals. Ore minerals are found within quartz veins ranging from few centimetres to tens of metres thick. The veins are characterized by crustiform, comb, vuggy, botroyidal, layering and bladed. Quartz is a dominant mineral as hydrothermal alteration in addition to illite, dickite, monmorillonite, kaolinite, chlorite, smectite, natrolite, nontronite, calcite, halloysite, palygorskite, muscovite, sepiolite, analcime, heulandite, clino-chlor, zircon, zoisite, laumontite, alunite, biotite and erionite. The presence of these secondary minerals could be classifi ed into prophylitic, argillic and advanced argillic types. Analytical result of gold–bearing quartz vein indicates higher content of gold (0.3%) and silver (400 ppm). In contrast, the content of sulphide minerals (Cu, Pb, and Zn) is very low (< 100 ppm). Combined geology, mineralogy, textures and alteration minerals, it is concluded that gold deposit in the area shows an indication of a low sulphidation epithermal type within Gunung Amas Formation.